Effectiveness Of Distribution Of Social Assistance For The Family Hope Program In An Effort To Maintain Accountability Of Reports (Case Study Of Social Service Of Sukabumi Regency): - Qudus, Dawam Harits Ruhul; Nurodin, Idang; Nugroho, Gatot Wahyu (Universitas Dehasen Bengkulu, 2024)
The distribution of social assistance for the Family Hope Program (PKH) by the Sukabumi Regency Social Service has generally been effective in increasing access for beneficiary families (KPM) to education and health and easing the economic burden of poor families. Although there are some challenges in reaching all families who meet the criteria, most beneficiaries are satisfied with the program. Overall, The Family Hope Program in Sukabumi Regency has successfully supported poverty alleviation efforts and improved community welfare, although improvement efforts are still needed to improve the effectiveness and efficiency of the program. The type of research used by the author is a qualitative descriptive method, the data processed is data obtained from the results of interviews and unstructured observations that will be analyzed qualitatively and described in descriptive form. The Social Service needs to continue to improve the verification and validation process of recipient data to ensure that assistance really reaches families in need. This process must involve the use of more sophisticated technology and applications, which can help minimize data errors and increase accuracy in determining beneficiaries. It is hoped that the distribution of PKH social assistance in Sukabumi Regency can run more effectively and efficiently and provide maximum positive impact on the welfare of people in need.